2012
DOI: 10.1097/brs.0b013e31825762b7
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chiropractic Spinal Manipulation in Older Adults Is Strongly Correlated With Supply

Abstract: Study Design Retrospective cross-sectional analysis of administrative data. Objective To examine the relationship between regional chiropractic supply and both use and utilization intensity of chiropractic services among Medicare beneficiaries. Summary of Background Data Numerous studies have documented trends and patterns in the utilization of chiropractic services in the United States, but little is known about geographic variation in the relationship between chiropractic supply and utilization. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 27 publications
(26 reference statements)
1
32
0
Order By: Relevance
“…The propensity score models used state chiropractor supply data for the interview start year, in addition to other known risk factors to estimate a probability of chiropractic use for each person-year observation. 4,5,4042 Once the propensity scores were estimated, the inverse probability of treatment weights (IPTW) were calculated and multiplied by the one-year sample weight provided in the MCBS to obtain a propensity score adjusted sample weight.…”
Section: Methodsmentioning
confidence: 99%
“…The propensity score models used state chiropractor supply data for the interview start year, in addition to other known risk factors to estimate a probability of chiropractic use for each person-year observation. 4,5,4042 Once the propensity scores were estimated, the inverse probability of treatment weights (IPTW) were calculated and multiplied by the one-year sample weight provided in the MCBS to obtain a propensity score adjusted sample weight.…”
Section: Methodsmentioning
confidence: 99%
“…SID suggests that new clinics may benefit from locating in areas already supplied with similar healthcare services, thus creating a pattern of supply and demand which is not geographically balanced. Much research has shown evidence of SID in conventional medicine (Léonard et al, 2009), and increased chiropractic supply has also been associated with increased chiropractic use (Whedon et al, 2012). However, analysis of SID requires measurement of both supply and demand, and therefore suggestion of the influence of SID in this study is only speculative.…”
Section: Spatial Pattern Analysesmentioning
confidence: 64%
“…These findings may also in turn have been influenced by other factors, such as the socioeconomic status of the surrounding residential areas creating a more desirable location for a clinic. A notable point is that Whedon et al (2012) only examined the use patterns of patients seeking care funded by health insurance.…”
Section: Potential Factors Influencing the Geographic Accessibility Omentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is not surprising considering the chiropractic profession began in the Midwest (specifically in Davenport, Iowa, which had the highest supply of chiropractors of all HRRs). 8,26,27 Given that the supply of physicians in general exhibits a different pattern, 28 it may raise questions about the role of chiropractic care in improving access to care (particularly in rural locales). Previous studies have examined the potential role of chiropractic care in improving access to care.…”
Section: Discussionmentioning
confidence: 99%